Effective method to culture infusoria, a highly potential starter feed for marine finfish larvae - Mukai, Yukinori; Sani, MZ; Mohammad Noor, Normawaty; Kadowaki, Shusaku (International Journal of Fisheries and Aquatic Studies, 2016)
This study was conducted to detect suitable protozoan species of infusoria as starter diet for early stage of marine finfish larvae. Infusoria were cultured using vegetables (Brassica pekinensis and Brassica chinensis) and dry fish meal with 30 ppt, 15 ppt saline water and freshwater in 40 liter aquaria. In the 30 and 15 ppt aquaria, Euplotes sp. was the dominant species and cell sizes were 60–80 μm. The densities of Euplotes sp. were 400–500 individuals/ml in the 30 ppt aquaria and 800-1300 individuals/ml in the 15 ppt aquaria. In both conditions, the high densities were maintained for 13 days. The densities of protozoa in saline water were higher in 15 ppt than in 30 ppt aquaria. The densities of protozoa cultured by our method was enough amount for early stage larvae of groupers and snappers. Therefore, this method is suitable for protozoa culture in small scale hatcheries.